2022
DOI: 10.11591/ijai.v11.i3.pp851-858
|View full text |Cite
|
Sign up to set email alerts
|

Integrating singular spectrum analysis and nonlinear autoregressive neural network for stock price forecasting

Abstract: <span>The main objective of stock market investors is to maximize their gains. As a result, stock price forecasting has not lost interest in recent decades. Nevertheless, stock prices are influenced by news, rumor, and various economic factors. Moreover, the characteristics of specific stock markets can differ significantly between countries and regions, based on size, liquidity, and regulations. Accordingly, it is difficult to predict stock prices that are volatile and noisy. This paper presents a hybri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…Hassani et al also found that SSA outperforms several singles models such as ARIMA, ETS, NN, Trigonometric Box-Cox ARMA Trend Seasonal (TBATS), and Fractionalized ARIMA (ARFIMA) to predict tourism demand in European countries. Fathi et al (2022) combined SSA and nonlinear autoregressive neural networks (NARNN) to predict 24 stock prices and compared them with ARIMA and NARNN. Their results also showed that SSA combined with NARNN provides better forecasting performance than ARIMA and NARNN.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hassani et al also found that SSA outperforms several singles models such as ARIMA, ETS, NN, Trigonometric Box-Cox ARMA Trend Seasonal (TBATS), and Fractionalized ARIMA (ARFIMA) to predict tourism demand in European countries. Fathi et al (2022) combined SSA and nonlinear autoregressive neural networks (NARNN) to predict 24 stock prices and compared them with ARIMA and NARNN. Their results also showed that SSA combined with NARNN provides better forecasting performance than ARIMA and NARNN.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their research employs machine learning methodologies to analyze the impact of economic uncertainty on stock market dynamics, highlighting the role of sentiment analysis in understanding stock market behavior. Asmaa Y. Fathi, Ihab A. El-Khodary, and Muhammad Saafan [4] explored the integration of singular spectrum analysis and nonlinear autoregressive neural networks for stock price forecasting. Their study represents an innovative approach to stock price prediction, emphasizing the importance of advanced computational techniques in financial modeling.…”
Section: Related Workmentioning
confidence: 99%